Re-establishing North Island kākā (Nestor meridionalis septentrionalis) in New Zealand : a thesis presented in fulfilment of the requirements for the degree of Master of Science in Conservation Biology, Massey University, Auckland, New Zealand - Joustra, Tineke (Massey University, 2018)
Recently there has been a global increase in concern over the unprecedented loss of biodiversity and how the sixth mass extinction event is mainly due to human activities. Countries such as New Zealand have unique ecosystems which led to the evolution of many endemic species. One such New Zealand species is the kākā (Nestor meridionalis). Historically, kākā abundance has been affected by human activities (kākā were an important food source for Māori and Europeans). Today, introduced mammalian predators are one of the main threats to wild kākā populations. Although widespread and common throughout New Zealand until the 1800’s, kākā populations on the mainland now heavily rely on active conservation management. The main methods of kākā management include pest control and re-establishments. This thesis evaluated current and past commitments to New Zealand species restoration, as well as an analysis of global Psittacine re-establishment efforts. First, I surveyed individuals involved in ecological restoration projects at multiple North Island locations, to establish their past and future commitments to the re-establishment of New Zealand native species. Secondly, another survey was distributed amongst several experts in the field of kākā re-establishment in New Zealand. Lastly, a systematic literature review was completed to establish which psittacine species have been part of re-establishment projects and the methods that were applied to these projects. The outcomes of the surveys and literature review contributed to the development of a draft recovery plan for North Island kākā. This 10-year plan is a guide for the Department of Conservation (DOC) and interest groups involved in conserving North Island kākā. Keywords: North Island kākā, Nestor meridionalis septentrionalis, threatened species recovery, recovery plan, conservation, stakeholder survey, expert survey, systematic review, Delphi technique, New Zealand
Keywords: Kaka (Bird) -- Conservation -- New Zealand -- North Island; Endangered species -- New Zealand -- North Island; Wildlife reintroduction -- New Zealand -- North Island; Wildlife conservation -- New Zealand -- North Island